Impact of Aldosterone Synthase Inhibitor FAD286 on Steroid Hormone Profile in Human Adrenocortical Cells - Brunssen, Coy; Hofmann, Anja; Peitzsch, Mirko; Frenzel, Annika; Ziegler, Christian G.; Brown, Nicholas F.; Weldon, Steven M.; Eisenhofer, Graeme; Willenberg, Holger S.; Bornstein, Stefan R.; Morawietz, Henning (Hormone and Metabolic Research, 2017)
Inhibition of aldosterone synthase (CYP11B2) is an alternative treatment option to mineralocorticoid receptor antagonism to prevent harmful aldosterone effects. FAD286 is the best characterized aldosterone synthase inhibitor. However, to date, no study has used sensitive liquid chromatography-tandem mass spectrometry to characterize in detail the effect of FAD286 on the secreted steroid hormone profile of adrenocortical cells. Basal aldosterone production in NCI-H295R cells was detectable and 9-fold elevated after stimulation with angiotensin II. FAD286 inhibited this increase, showing a maximal effect at 10 nmol/l. Higher concentrations of FAD286 did not further reduce aldosterone concentrations, but showed a parallel reduction in corticosterone, cortisol and cortisone levels, reflecting additional inhibition of steroid-11β-hydroxylase (CYP11B1). Pregnenolone, progesterone and 17-OH-progesterone levels remained unaffected. In conclusion, the aldosterone synthase inhibitor FAD286 lowers angiotensin II-induced aldosterone concentrations in adrenocortical cells but the relative lack of selectivity over CYP11B1 is evident at higher FAD286 concentrations.
Keywords: aldosterone; steroid hormones; mineralocorticoids; glucocorticoids; adrenal cortex